The Contribution of Women Authors to the Discovery of People of the Female Sex in German-Speaking Literature Since 1945 - Ingeborg Drewitz (Studies in 20th & 21st Century Literature, 1985)
The paper proceeds from the assumption that women write differently from men; that, as Virginia Woolf asserted, if one were to place two texts side by side, one by a woman and one by a man, one would be able to ascertain the sex of the author. This paper attempts to shed some light on the reasons why this should be so: is it a result of innate differences in personality, or in socialization, or both? It also examines in some detail (and this is its main burden) the different subjects that women in the Federal Republic of Germany after 1945 choose to write about and the different ways in which they treat these subjects. Extensive quotations from a number of important women writers are given in order to convey a sense of the texture of this writing to an English-speaking audience.
Keywords: Virginia Woolf; women; men; write; different; socialization; Federal Republic of Germany; 1945; after 1945; English-speaking audience; BRD